2009
DOI: 10.2139/ssrn.1465996
|View full text |Cite
|
Sign up to set email alerts
|

Executive Compensation and Business Policy Choices at U.S. Commercial Banks*

Abstract: This study examines whether and how the terms of CEO compensation contracts at large commercial banks between 1994 and 2006 influenced, or were influenced by, the risky business policy decisions made by these firms. We find strong evidence that bank CEOs responded to contractual risk-taking incentives by taking more risk; bank boards altered CEO compensation to encourage executives to exploit new growth opportunities; and bank boards set CEO incentives in a manner designed to moderate excessive risk-taking. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 8 publications
3
38
0
Order By: Relevance
“…This result is consistent with the implication of agency theory as well as the evidence provided from other developed countries outside Australia (Jensen and Murphy 1990;Coles et al, 2006;Basu et al, 2007;DeYoung et al, 2013), but in contract to findings of most prior published literature in the Australian (Capezio et al, 2007;Craswell et al, 1997;O"Neill and Iob, 1999).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…This result is consistent with the implication of agency theory as well as the evidence provided from other developed countries outside Australia (Jensen and Murphy 1990;Coles et al, 2006;Basu et al, 2007;DeYoung et al, 2013), but in contract to findings of most prior published literature in the Australian (Capezio et al, 2007;Craswell et al, 1997;O"Neill and Iob, 1999).…”
Section: Resultssupporting
confidence: 91%
“…Therefore, corporate performance should be positively associated with key management personnel remuneration. Although some studies of developed countries outside Australia suggested a weak pay-performance (Gregg et al, 1993;Conyon et al, 1995), Most studies taken in developed countries found a positive association between key management personnel remuneration and corporate performance (Jensen and Murphy 1990;Conyon, 1997;Coles et al, 2006;Basu et al, 2007;DeYoung et al, 2013;McKnight, 1996;Ingham and Thompson, 1995), which is consistent with the implication of agency theory.…”
Section: Resultsmentioning
confidence: 59%
See 3 more Smart Citations